Construction of knowledge base to visualize the cross-cultural difference over information - ZIRAN FAN; TAKAYUKI FUJIMOTO (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This research hopes to offer solutions to these issues based on real-world examples of data discrepancies between Japan and China. We’re building a database of information to close the gap in Japan and China’s understanding of each other across all disciplines.Method: However, it is challenging to implement a method that addresses all aspects of cross-cultural information gaps, so it is important to find a mechanism that satisfies the criteria for information quantity, immediacy, and practicality to address the intercultural knowledge gap.Findings: Results show that the proposed system constructs the knowledge base with the high-level immediacy to renew the information organically depending on the situation. This improves practical utility by storing information that broadly matches users’ needs. Through the use of artificial intelligence, it delivers content that is tailored to each user based on their current activity. Data can be stored, updated, and searched in the system, but that’s not all it can do. To fully realise the system’s interactivity, we integrate post/read/reuse functions for the user comments. As a result of this research, we will be able to implement a knowledge base to address issues with cross-cultural communication.Implications/Novel contribution: The innovative aspect of this study is that it proposes an immersive interface for consumers and expects it to be a powerful instrument for their cross-cultural exchange of ideas.